The Relationships Between Hyperprolactinemia, Metabolic Disturbance, and Sexual Dysfunction in Patients With Schizophrenia Under Olanzapine Treatment - Wu, Tzu-Hua; Lin, Chieh-Hsin; Goh, Kah Kheng; Chen, Cynthia Yi-An; Chen, Chun-Hsin; Lane, Hsien-Yuan; Lu, Mong-Liang (Frontiers in Pharmacology, 2021)
The aim of the study was to assess the relationship between prolactin levels and sexual dysfunction in patients with schizophrenia who use olanzapine medication. The potential risk factors of hyperprolactinemia and sexual dysfunction were also investigated. Patients with schizophrenia undergoing olanzapine monotherapy were invited to participate in this cross-sectional study. The Arizona Sexual Experiences Scale (ASEX) and the Positive and Negative Syndrome Scale were used to evaluate subjective sexual dysfunction and psychopathology, respectively. Levels of prolactin and metabolic parameters were also measured. In total, 279 participants with schizophrenia were recruited. The overall incidences of hyperprolactinemia, sexual dysfunction, and metabolic syndrome were 51.6, 53.8, and 43.7%, respectively. Higher ASEX scores, higher insulin levels, female sex, and younger age were associated with hyperprolactinemia. Prolactin level was significantly correlated with ASEX score. Elevated prolactin levels, concomitant antidepressant, increased insulin resistance, longer illness duration, and female sex were associated with sexual dysfunction. Female participants recorded higher levels of sexual dysfunction than their male counterparts did, whereas male participants had comparatively lower prolactin levels and lower rates of spousal partnership. Hyperprolactinemia, metabolic syndrome, and sexual dysfunction are prevalent in patients with schizophrenia treated with olanzapine. Clinicians should maintain awareness of these problems and monitor them regularly with their patients.